2001
DOI: 10.3998/ark.5550190.0002.a08
|View full text |Cite
|
Sign up to set email alerts
|

A convenient method for the synthesis of nitrones by oxidation of N,N-disubstituted hydroxylamines with N-tert-butylphenylsulfinimidoyl chloride

Abstract: Dedicated to Professor AbstractVarious N,N-disubstituted hydroxylamines were smoothly oxidized to the corresponding nitrones under mild conditions (at -78 °C) by using N-t-butylbenzenesulfinimidoyl chloride and DBU in methylene chloride. Intermolecular 1,3-dipolar cycloaddition of thus formed nitrones with certain kinds of olefines was also performed by one-pot procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Snider et al have reported a direct method whereby the b-vinylic hydrogens of enones were substituted with alkyl groups by using alkenes and EtAlCl 2 , but applicable alkenes were limited to trisubstituted ones. 11 In 2000, we introduced N-tert-butylbenzenesulfinimidoyl chloride (1) as a new and variable oxidation (dehydrogenation) reagent for organic synthesis, 12 and various oxidation reactions such as oxidation of alcohols, 13 amines, 14 and hydroxylamines 15 were investigated. Among the 1-mediated oxidations, dehydrogenation of carbonyl compounds to the corresponding a,b-unsaturated compounds is notable because it proceeds under rather mild conditions (278 uC) and in a one-pot manner: 16 that is, it is carried out by the reaction of 1 and lithium enolates generated from carbonyl compounds with LDA.…”
mentioning
confidence: 99%
“…Snider et al have reported a direct method whereby the b-vinylic hydrogens of enones were substituted with alkyl groups by using alkenes and EtAlCl 2 , but applicable alkenes were limited to trisubstituted ones. 11 In 2000, we introduced N-tert-butylbenzenesulfinimidoyl chloride (1) as a new and variable oxidation (dehydrogenation) reagent for organic synthesis, 12 and various oxidation reactions such as oxidation of alcohols, 13 amines, 14 and hydroxylamines 15 were investigated. Among the 1-mediated oxidations, dehydrogenation of carbonyl compounds to the corresponding a,b-unsaturated compounds is notable because it proceeds under rather mild conditions (278 uC) and in a one-pot manner: 16 that is, it is carried out by the reaction of 1 and lithium enolates generated from carbonyl compounds with LDA.…”
mentioning
confidence: 99%
“…15 The next step was the construction of the nitrone unit 7 utilizing a convenient and mild method developed by Mukaiyama and coworkers. 16 Gratifyingly, the use of N-t-butylbenzenesulfinimidoyl chloride 21 17 at À78 1C resulted in a complete regioselective formation of nitrone 7 due to steric encumbrance and an immediate intramolecular [1,3]-dipolar cycloaddition 15a,18,19 was observed. Finally, the removal of silyl group was performed using tetrabutylammonium fluoride to give virosaine A (1) in a good yield of 81% over two steps.…”
mentioning
confidence: 99%